A Prospective Randomized Study of Brain Tissue Oxygen Pressure-Guided Management in Moderate and Severe Traumatic Brain Injury Patients. (27th August 2015) - Lin, Chien-Min; Lin, Ming-Chin; Huang, Sheng-Jean; Chang, Cheng-Kuei; Chao, Dan-Ping; Lui, Tai-Ngar; Ma, Hsin-I; Liu, Ming-Ying; Chung, Wen-Yuh; Shih, Yang-Hsin; Tsai, Shin-Han; Chiou, Hung-Yi; et al.
Abstract : The purpose of this study was to compare the effect of PbtO2 -guided therapy with traditional intracranial pressure- (ICP-) guided treatment on the management of cerebral variables, therapeutic interventions, survival rates, and neurological outcomes of moderate and severe traumatic brain injury (TBI) patients. From 2009 to 2010, TBI patients with a Glasgow coma scale <12 were recruited from 6 collaborative hospitals in northern Taiwan, excluding patients with severe systemic injuries, fixed and dilated pupils, and other major diseases. In total, 23 patients were treated with PbtO2 -guided management (PbtO2 > 20 mmHg), and 27 patients were treated with ICP-guided therapy (ICP < 20 mmHg and CPP > 60 mmHg) in the neurosurgical intensive care unit (NICU); demographic characteristics were similar across groups. The survival rate in the PbtO2 -guided group was also significantly increased at 3 and 6 months after injury. Moreover, there was a significant correlation between the PbtO2 signal and Glasgow outcome scale-extended in patients from 1 to 6 months after injury. This finding demonstrates that therapy directed by PbtO2 monitoring is valuable for the treatment of patients with moderate and severe TBI and that increasing PaO2 to 150 mmHg may be efficacious for preventing cerebral hypoxic events after brain trauma.